Knowledge-Attitude Health Behaviour And Vitamin D Status During Epidemic Covid-19 - Lorensia, Amelia; Septinellya, Cinthya Farah; Suryadinata, Rivan Virlando (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2025)
Vitamin D deficiency or vitamin D deficiency can increase the incidence of respiratory diseases. The of individuals have less knowledge and attitudes towards health problems. The objective was determine relationship vitamin D status and knowledge-attitudes health Behaviour about vitamin D. This type of research was a cross-sectional research design. The research location used in this study was around the Surabaya area starting in March-July 2022. The research location was carried out in Rungkut District, Surabaya, Indonesia. The variables were vitamin D status and knowledge and attitudes on smoking health Behaviour about vitamin D. The relationship between vitamin D status and knowledge-attitudes on smoking health Behaviour about vitamin D using a contingency coefficient. There was no significant relationship with vitamin D status and knowledge on smoking health Behaviour about vitamin D (p=0.685), but there was a significant relationship with vitamin D status and attitude on smoking health Behaviour about vitamin D, but the relationship was low or weak (p=0.000). A positive attitude will reduce the risk of vitamin D deficiency which can boost the immune system during the COVID-19 pandemic.